2008
DOI: 10.1002/cphc.200800491
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis of SAPO‐11 and AlPO‐11: Aspects of Reactor Engineering

Abstract: AlPO-11 and SAPO-11 are synthesized using microwave heating. The effects of precursor volume, reaction temperature, reactor geometry, stirring, applicator type and frequency on the microwave synthesis of SAPO-11 and AlPO-11 are studied. The nucleation time and crystallization rate are determined from crystallization curves for SAPO-11 (and/or AlPO-11), for the various parameters investigated. Increasing volume of the reacting material decreases the reaction rate of SAPO-11 at 160 degrees C. In particular, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…[51] There are only few studies that compare the influence of microwave-assisted and conventional heating on the crystallization rate, and the described data is not consistent. In ex situ quenching experiments on the crystallization of Fe-MIL-53 [45] and AlPO-11, [52] higher activation energies under MW conditions were reported. Nevertheless, MW heating led to an acceleration of the crystallization.…”
Section: Plotting Lna C H T U N G T R E N N U N G [àLna C H T U N G Tmentioning
confidence: 97%
See 1 more Smart Citation
“…[51] There are only few studies that compare the influence of microwave-assisted and conventional heating on the crystallization rate, and the described data is not consistent. In ex situ quenching experiments on the crystallization of Fe-MIL-53 [45] and AlPO-11, [52] higher activation energies under MW conditions were reported. Nevertheless, MW heating led to an acceleration of the crystallization.…”
Section: Plotting Lna C H T U N G T R E N N U N G [àLna C H T U N G Tmentioning
confidence: 97%
“…Possible explanations are the increase of the concentration of reaction sites (number of nuclei) and a higher mobility of the reactants in the microwave field that could lead to an increase of the collision frequency. [49,52,53] …”
Section: Plotting Lna C H T U N G T R E N N U N G [àLna C H T U N G Tmentioning
confidence: 98%
“…However, accelerated MW-syntheses of Cu 2 O [16], molecular sieves like AlPO-11 and SAPO-11 [17] and metal-organic frameworks (MOFs) such as ironbenzenedicarboxylate [18] and copper-benzenetricarboxylate [19] are mainly due to a very large increase in pre-exponential factors (even with increased E a ). Very recently, Ahnfeldt et al [20] have shown the accelerated synthesis of a MOF (CAU-1-(OH) 2 ) with MWs is due to an increase of pre-exponential factor.…”
Section: Resultsmentioning
confidence: 99%
“…6). Work submitted for publication [42], on the effect of reactor and synthesis parameters on the microwave synthesis of SAPO-11 will demonstrate the interaction of microwaves with the crystallization and nucleation rates.…”
Section: Discussionmentioning
confidence: 99%